1979
DOI: 10.1104/pp.63.5.903
|View full text |Cite
|
Sign up to set email alerts
|

Isoenzymes of Pyruvate Kinase in Etioplasts and Chloroplasts

Abstract: Isoenzymes of pyruvate kinase from green leaves of castor bean and etiolated leaves of pea plants have been separated by ion filtration chromatography. One of the isoenzymes is localzed in the plastid, whereas the other is in the cytosol. The cytosolic enzyme has a pH optimum from pH 7 to pH 9, and is able to utilize nucleotides other than ADP as the phosphoryl acceptor. The plastid enzyme has a much sharper optimum at pH 8, and is less efficient at using alternative nucleotides. The plastic pyruvate kinase, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
3

Year Published

1982
1982
2022
2022

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 13 publications
(12 reference statements)
3
34
0
3
Order By: Relevance
“…Although the evidence is as yet fragmentary, it seems that the situation is similar in other developing oilseeds (at least sunflower, safflower, soybean, and cotton seeds) and in some chloroplasts (10) and chromoplasts (15) as well. Nishimura and Beevers (21) recently reported that germinating castor oil seeds contain plastid and cytosolic isozymes of the enzymes of sugar-phosphate metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…Although the evidence is as yet fragmentary, it seems that the situation is similar in other developing oilseeds (at least sunflower, safflower, soybean, and cotton seeds) and in some chloroplasts (10) and chromoplasts (15) as well. Nishimura and Beevers (21) recently reported that germinating castor oil seeds contain plastid and cytosolic isozymes of the enzymes of sugar-phosphate metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been possible by using anion-exchange chromatography to separate a11 other chloroplast/cytosol isoenzymes of sugar phosphate metabolism investigated to date, e.g. starch phosphorylase (Steup et al, 1980;Mateyka and Schnarrenberger, 1984), phosphoglucomutase (Mühlbach and Schnarrenberger, 1978), Glc-P isomerase (Schnarrenberger and Oeser, 1974), FBPase (Latzko et al, 19741, FBP aldolase (Kriiger and Schnarrenberger, 1983;Lebherz et al, 1984;Schnarrenberger and Kriiger, 1986), hexokinase (Schnarrenberger, 1990), G6PDH and 6PGDH (Schnarrenberger et al, 1973(Schnarrenberger et al, , 1975Simcox et al, 1977;Simcox and Dennis, 1978;Nishimura and Beevers, 19811, glyceraldehyde-3-P dehydrogenase (Miernyk and Dennis, 19821, 3-phosphoglycerate kinase (Miernyk and Dennis, 1982;Kopke-Secundo et al, 1990;Morrow and Bradbeer, 1990), triose-P isomerase (Kurzok and Feierabend, 1984), pyruvate kinase (Ireland et al, 1979), and enolase and phosphoglycerate mutase (Miernyk and Dennis, 1982;Plaxton, 1989). It is conceivable, yet we consider it highly unlikely, that isoenzymes for transaldolase, transketolase, Rib-5-P isomerase, and ribulose-5-P epimerase exist but are undetectable.…”
Section: Resultsmentioning
confidence: 99%
“…A possible explication is related with BAP action on the biosynthesis of fatty acids 20 , it could be a factor that influence in the synthesis of enzymatic proteins such as piruvate kinases related with the formation of carbonated chains in the biosynthesis of fatty acids in plants 21 .…”
Section: Discussionmentioning
confidence: 99%